Physical Modeling Approach for Assessing the Effect of Climate Change on Groundwater at Coastal Area - May, Raksmey; Siti Aishah, Sahul Hamid (2018)
Seawater intrusion has brought a great deal of attention globally with the worsening effect of rising sea level and changing of climates. Global climate change which has caused the unevenness increased in extreme events such as droughts and floods has anticipated water resources to become impaired. In this study, under the influence of climate change, a shallow unconfined groundwater was laid out orderly to investigate the saltwater intrusion phenomena in coastal aquifers. Experiments were conducted using laboratory rectangular model tank filled with fresh water, well-sorted sand and salt water into three separate chambers. In spite of the fact that numerous experimental procedures have been acquired to investigate the transient development of the saltwater interface in unconfined aquifers, none of them has tackled the possibilities of applying the climate change effect. The main focus of this particular investigation is to compare the relation of recharge and rising of sea level on the behavior of the saltwater interface in the unconfined aquifer from laboratory experiment with the normal cases of flood and the sea level rise as well as the drought and sea level rise. Simulation on the projected rising of sea level due to the climate change leads to significant intrusion outcomes of 52.4% with a toe of the saltwater wedge (TOE) distance of 0.54 m; however, an increase in the magnitude of precipitation rates and freshwater head can ultimately recharge the groundwater. This mitigates the changes of 49% in the saltwater-freshwater interface (SFI) with a receding distance of 0.22 m.